Gas-fired chemical looping combustion with supercritical CO2 cycle - Khallaghi, Navid; Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2019)
Oxy-fuel combustion is currently gathering attention as one of the promising options for capturing CO2 efficiently, when applied to power plants, for subsequent carbon sequestration. However, this option requires a large quantity of high-purity oxygen that is usually produced in an energy-intensive air separation unit (ASU). Chemical looping combustion (CLC) is a technology with the potential of reducing the costs and energy penalties associated with current state-of-the-art cryogenic ASUs. In this work, the techno-economic performance of a natural gas-fired oxy-combustion cycle with cryogenic ASU is compared with that based on CLC. Two natural gas-fired cycles are considered: (i) staged oxy-fuel natural gas combined cycle as a reference; and (ii) gas-fired CLC with supercritical CO2 cycle. The process models were developed in Aspen Plus® in order to evaluate the thermodynamic performance of the proposed system and to benchmark it against the reference cycle. The results show that the net efficiency of the proposed cycle, including CO2 compression, is more than 51%, which is comparable to that of a conventional natural gas combined cycle with CO2 capture and 2.7% points higher than that of the reference cycle. Moreover, the economic evaluation indicates that a reduction in levelised cost of electricity from £38.3/MWh to £36.1/MWh can be achieved by replacement of the ASU-based oxy-fuel system with CLC. Hence, gas-fired CLC with a supercritical CO2 cycle has high potential for commercialisation.
Keywords: Carbon capture; Oxy-fuel turbine; Cryogenic ASU; Chemical looping combustion; Natural gas combined cycle; Oxygen production